Representation of Millennial Preachers in Preaching Content on the Instagram Account @husein_jafar - Sultoni, Muhammad Wildan (Tebuireng: Journal of Islamic Studies and Society, 2026)
The development of social media has brought significant changes in the practice of Islamic da'wah, particularly through the Instagram platform, which allows the dissemination of religious messages in a visual, interactive, and easily accessible manner to the younger generation. This study aims to analyze the representation of millennial da'wah preachers in da'wah content on the Instagram account @husein_ja'far. The study uses a descriptive qualitative approach with Roland Barthes's semiotic analysis method focusing on denotative, connotative, and mythical meanings. Stuart Hall's representation theory is used to understand the process of meaning formation in digital da'wah content. The research data were obtained from several Instagram posts by Habib Husein Ja'far featuring themes of religious tolerance, spirituality, the unity of Muslims, and religious freedom. The results show that the representation of millennial da'wah preachers is built through communicative characteristics, adaptability to technological developments, closeness to the younger generation, and the ability to package religious messages through humor, dialogue, and creative content. At the denotative level, the content displays daily activities and cross-community collaboration. At the connotative level, the visuals and narratives used contain messages of religious moderation, inclusivity, and the importance of humanitarian values. Meanwhile, at the mythical level, the content constructs the ideology that Islam is a tolerant, peaceful religion, and relevant to life in a digital society. This study concludes that the Instagram account @husein_ja'far represents a millennial preacher who is humanistic, moderate, and able to utilize digital media as an effective means of preaching. This representation demonstrates the transformation of preaching from a conventional model to a more participatory, contextual digital preaching model that aligns with the characteristics of modern society.